GERAKAN LITERASI PANCASILA: UPAYA MENUMBUHKAN KESADARAN BELA NEGARA DI KALANGAN SISWA SEKOLAH MENENGAH PERTAMA NEGERI 3 KOTA GORONTALO - Saleh Al Hamid; Roni Lukum (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
Students of SMP Negeri 3 Gorontalo City were the primary participants in this community engagement initiative aimed at fostering national defense awareness among young learners. Instilling Pancasila values and national defense consciousness is fundamental in shaping the character of Indonesia's younger generation. As the ideological foundation of the nation, Pancasila plays a crucial role in youth character development. However, amid globalization and the digital revolution, there has been a decline in the understanding of Pancasila values due to the infiltration of foreign cultures. This phenomenon has weakened nationalism and national defense awareness among students, including those at SMP Negeri 3 Gorontalo City. The community engagement activities, conducted in the school hall, followed these stages: (1) Coordination with SMP Negeri 3 Gorontalo City, beginning with a formal request letter addressed to the school principal; (2) Preliminary survey through questionnaires and interviews to assess students' knowledge of Pancasila and national defense. As the speaker, I conducted socialization sessions for the students with the following objectives: (1) Introducing and implementing the Pancasila Literacy Movement as a concrete step to cultivate national defense awareness; (2) Establishing the Pancasila Literacy Movement as an effective educational tool for fostering national defense consciousness; (3) Creating a learning community with a comprehensive understanding of national defense, reflected in attitudes of tolerance, unity, and a willingness to contribute to national progress. The results showed that students began to recognize that national defense extends beyond military efforts—it also encompasses patriotism, respect for diversity, and active contributions to national development through the application of Pancasila values.